Dillenia suffruticosa dichloromethane root extract reduced metastasis of 4T1 cells to the liver and heart without causing toxicity in female BALB/c mice - Saiful Yazan, Latifah; Roslie, Siti Hanani; Mohd Ali, Razana; Mohd Khaidi, Ahmad Amir Shabrin; Ong, Yong Sze; Zakarial Ansar, Fatin Hannani; Esa, Nurulaidah; Sapuan, Sarah; Gopalsamy, Banulata (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2019)
Introduction: Breast cancer is ranked first among other cancers in women. Ineffectiveness of current treatments and adverse effects such as multiple organ failure and nephrotoxicity are the common problems faced in cancer therapy. Therefore, alternatives to treat breast cancer metastasis with fewer toxic effects are actively sought-after. Dillenia suffruticosa (DS) commonly known as ‘Simpoh air’ has been a traditional remedy for cancer growth. Therefore, this study investigated the metastasis inhibiting properties of DS root dichloromethane extract (DCMDS) in tumour bearing female BALB/c mice and sub-acute multiple dose oral toxicity upon treatment with this extract. Methods: Forty-eight tumour bearing mice were given either oral treatment of DCMDS (50, 100 and 200 mg/kg) or doxorubicin (2 mg/kg) for 28 days and the degree of metastasis was analysed in each group. Thirty other female BALB/c mice were treated with DCMDS (50, 100 and 200 mg/kg) and the general behaviours, biochemical, haematological and histopathological changes were observed. Data were analysed with One-way ANOVA and Dunnet’s test where p<0.05 was considered significant. Results: All doses of DCMDS showed lowered metastatic cells in liver and DCMDS at (50 and 100 mg/kg) had less metastatic cells in the heart compared to doxorubicin (2 mg/kg). All DCMDS treated groups showed no abnormal behaviours and all tested physiological parameter values fall within the normal ranges. Conclusion: DCMDS reduced metastasis of 4T1 cells to the liver and heart better than doxorubicin without causing toxicity. This study highlights that DCMDS is a promising drug to be further developed for cancer therapy.